Re-examining Amnesty and Abolition Practices in Indonesia: A Normative Evaluation and Framework for Procedural Guidance - Putra, Steinly Suwanto; Suarda, Gede Widhiana; Rato, Dominikus; Anggono, Bayu Dwi; Siagian, Ruben Cornelius (Universitas Islam Indonesia, 2025)
The granting of amnesty and abolition in Indonesia is a presidential prerogative under Article 14 of the 1945 Constitution. Its practice has exhibited complex and diverse patterns throughout Indonesia’s political history, from the Soekarno era to the Prabowo Subianto administration. It has generated controversy regarding the rule of law, substantive justice, transparency, and the protection of victims’ rights. This study aims to analyze the practice of amnesty and abolition from historical and juridical perspectives, evaluate its implications for the principle of the rule of law, and identify potential abuses of presidential discretion. Methods include case studies, comparative juridical analysis, and review of legal documents such as presidential decrees, Article 14 of the 1945 Constitution, court decisions, BPUPKI minutes, and legal literature. The analysis was conducted using historical, normative, and descriptive argumentative approaches. The results show that political considerations often influence the practice of amnesty and abolition, can create a perception of legal uncertainty, and that the DPR plays only a formal role. Patterns of granting amnesties differ by era: political stabilization (Soekarno, Soeharto); political rights rehabilitation (Habibie, Abdurrahman Wahid/Gus Dur); peace integration (SBY); and individual justice and human rights considerations (Jokowi, Prabowo). This research proposes a legal bureaucratic framework to strengthen transparency, accountability, and substantive justice. In conclusion, amnesties and abolitions should be implemented with due regard for justice, transparency, legal certainty, and public oversight to prevent abuse of power and to maintain public trust in the legal system.